Why should everybody learn Last Aid to provide end-of-life care? - Georg Bollig; Erika Zelko (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Today most people would like to die at home [1]. Although the majority of people would prefer to die at home most people die in institutions as hospitals or nursing homes [2-5]. Main barriers for home death are present problems like breathlessness and most important lack of relatives. From our experience in palliative care relatives are often afraid to take care of dying people at home. Most relatives are not familiar where to get available professional support from the healthcare system and do not know how to contact and cooperate with specialised palliative care teams at home.